Intervención del terapista respiratorio en paciente femenino de 66 años con insuficiencia respiratoria aguda asociada a covid-19. - Carbo Icaza, Karen Michel (2023)
Acute respiratory failure (ARI) is the inability of the respiratory organs to perform their main function, that is, the exchange of oxygen and carbon dioxide between the surrounding air and the circulating blood, which must be carried out efficiently and sufficiently according to the metabolic factor. to the needs of the body, taking into account the age of the patient. This study is based on the intervention of the respiratory therapist in a 66-year-old female patient with acute respiratory failure associated with Covid-19. Carrying out this research work is justified since today, despite the existence of immunization vaccines to avoid complications in the health status of patients who contract this respiratory pathology, Covid-19 continues to be a serious health problem. Correct clinical evaluation and further investigation of the signs and symptoms presented by these patients will greatly contribute to the accurate diagnosis of patients suspected of having this pathology. The intervention of a respiratory therapist plays an important role in the treatment of patients with this disease, since the administration of oxygen therapy is very important for the recovery of these patients. Proper management of these patients with adequate pharmacological therapies and respiratory therapy techniques will help us to improve their clinical picture.